Effect of Confined Optical Phonons on Photo-Stimulated Ettingshausen Effect in Rectangular Quantum Wires with A Perpendicular Magnetic Field - Nguyet Anh, Nguyen Thi; Tung, Luon Van; Bau, Nguyen Quang; Dien, Tang Thi (VNU Journal of Science: Mathematics - Physics; Vol 39 No 1DO - 10.25073/2588-1124/vnumap.4783, 2023)
We applied the quantum kinetic equation method to investigate the influence of confined optical phonons (confined OP) on the photo-stimulated Ettingshausen effect in rectangular quantum wires (RQW) subjected to a perpendicular magnetic field. We considered the case where the confined electrons-confined OP scattering is the dominant mechanism. Analytical expressions for the kinetic tensors, the EC are obtained. The EC is a function of external fields, the temperature of the system, especially the quantum numbers m 1 and m 2 characterizing confined OP. When the width of the wire increases to infinity, the results of the bulk semiconductors can be gained. The numerical results are numerically evaluated and discussed for the GaAs/AlGaAs RQW. The magnitude of the resonance peaks has been increased for each value of m 1 , m 2 , found when examining the dependence of the EC on the photon energy. Furthermore, the EC is decreased considerably when the amplitude of EMW increases, which is obtained when investigating the dependence of the EC on the amplitude of EMW (laser). These results are important for further researches and could be helped to complete the theory of the thermo - magnetoelectric effects in the low dimensional system.